An insight into population structure and genetic progress of Argentinean Holstein cattle - Pardo, Alan Maxs; Casanova, Daniel; Rubio, Natalia; Andere, Cecilia; Rodríguez, Edgardo; Corva, Pablo (Wiley, 2023)
The objective of the present study was to investigate the most critical issues associated with the limited genetic progress evidenced in the Argentinean Holstein (“Holando Argentino”) breed in the last 20 years (only 26% of the phenotypic trend in milk yield was due to genetics). The study comprised the analysis of population structure, realized genetic selection differentials, genetic progress and partition of genetic trends by sex and country of origin from 1936 to 2019 (1,045,582 records; 24,680 sires and 619,322 dams in the pedigree). Average inbreeding steadily increased in the last 15 generations (ΔF = 0.6%, which translates to Ne = 75). Partition of genetic trends revealed that local genetics made a negligible contribution to genetic progress, which for most traits was highly dependent on imported genetics (>80%). Mean generation intervals were fairly constant until 2009 (8–9 years for males and 5–6 years for females, respectively) and then decreased, especially in the paths of sires of bulls and dams of bulls (to 5 and 4 years, respectively) mostly due to the influence of imported sires. The reduction in generation intervals was counterbalanced by a marked deterioration of realized selection differentials, particularly in the path of sires of bulls that nevertheless made the largest contribution to genetic progress. In the last 20 years, realized selection differentials in this path went from 533.6 to 170.8 kg for milk yield and from 16.7 to 13.3 kg for protein yield (1.7–0.5 and 1.6–1.3 standard deviation units, respectively). Among all considered traits (milk yield, fat yield, protein yield, stature, final score and daughter pregnancy rate) in the analysed period, annual genetic gain was negative for milk yield, fairly constant for composition and conformation traits, and positive only in the case of daughter pregnancy rate. Considered together, these results suggest that limited genetic progress is due to the absence of a sound breeding programme that includes genomic selection and a carefully defined selection objective, together with the absence of stronger regulations in germplasm importation; however, other factors such as potential genetics by environment interactions cannot be ruled out.